Teorias do bem estar e comércio internacional - Martins, Mauro Sebastião [UNESP] (2008)
The present monograph contents research in international trade and welfare economics models and theories, primary and secondary bibliographies are contemplated. The theories and models are the principal core in this study in those economics knowledgeís fields. The work is the analyses of confluences, intersections and common elements that exist in the theories and models. The introduction and first chapter has a study of models and theories in international trade from Ricardo, Ohlin, Samuelson until the contemporary studies. The first chapter is a study of theoretical and analytical models of welfare economics. The second chapter is the conclusion of the studies of introduction and first chapter whit the development of one study about the confluences of the international trade and welfare economics theoretical models in contemporary studies. Chapter later is a study of international trade and welfare economics confluences in actual theoretical models from old theoretical models.